Efek Pemberian Dosis Pupuk NPK Phonska 15-15-15 Terhadap Pertumbuhan Dan ProduksiTanaman Terung Ungu Mustang F1 (Solanum Melangona L.) - Aslan Clinton Hutauruk; Yusmaidar Sepriani; Fitra Syawal Harahap (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
The effect of the dosage of NPK Phonska 15-15-15 on the superior eggplant (Solanum Melongena L). This research was conducted at the Mangga Bawah Junction in the Desert. This research will be carried out from April to June 2020. The method used is the average height of the eggplant plants in NPK Phonska 15-15-15 fertilizer treatment. It can be seen that the highest value and the lowest value for eggplant plants aged 5 weeks is the highest value at P2 of 56 cm and the lowest value at P0 is 35 cm. The average of the number of branches of eggplant in NPK Phonska 15-15-15 treatment can be seen the highest value and the lowest value in the 5 week old eggplant plant, namely the highest value at P3 of 6 stalks and the lowest value at P0 of 1 stalk. The average weight of the eggplant plant showed that the results of the average difference test from the height of the eggplant plant in the NPK Phonska 15-15-15 treatment can be seen that the highest value and the lowest value in the eggplant plant were the highest value at P3 of 4.20 cm and the value the lowest at P0 of 1.30cm Key words: NPK Phonska 15-15-15, Solanum melongena L.